2022
DOI: 10.3390/ijerph192114139
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Low Birthweight in Low-and-Middle Income Countries in South Asia

Abstract: Child with Low Birth Weight (LBW) has a higher risk of infant mortality, learning difficulties in childhood due to stunted growth and impaired neurodevelopment, is more likely to develop heart diseases and diabetes in adulthood. This study aimed to evaluate the latest demographic and health surveys (DHSs) across multiple countries in South Asia to determine the factors associated with LBW among these countries. Latest available DHS data across Afghanistan (2015, n = 29,461), Bangladesh (2018, n = 20,127), Nepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Penelitian telah menunjukkan bahwa kondisi ekonomi keluarga dapat memiliki dampak yang signifikan terhadap akses terhadap nutrisi yang memadai, perawatan kesehatan, dan lingkungan yang mendukung pertumbuhan dan perkembangan anak (34).Keluarga dengan pendapatan rendah sering kali menghadapi keterbatasan dalam memenuhi kebutuhan gizi yang memadai, akses terhadap pangan bergizi, layanan kesehatan, serta lingkungan yang bersih dan sehat. Ketidakmampuan untuk memenuhi kebutuhan ini dapat menyebabkan anak-anak rentan terhadap stunting dan masalah gizi lainnya (35,36).…”
Section: Pengaruh Pendapatan Keluarga Terhadap Kejadian Stuntingunclassified
“…Penelitian telah menunjukkan bahwa kondisi ekonomi keluarga dapat memiliki dampak yang signifikan terhadap akses terhadap nutrisi yang memadai, perawatan kesehatan, dan lingkungan yang mendukung pertumbuhan dan perkembangan anak (34).Keluarga dengan pendapatan rendah sering kali menghadapi keterbatasan dalam memenuhi kebutuhan gizi yang memadai, akses terhadap pangan bergizi, layanan kesehatan, serta lingkungan yang bersih dan sehat. Ketidakmampuan untuk memenuhi kebutuhan ini dapat menyebabkan anak-anak rentan terhadap stunting dan masalah gizi lainnya (35,36).…”
Section: Pengaruh Pendapatan Keluarga Terhadap Kejadian Stuntingunclassified
“…Low birth weight (LBW) of children poses a serious public health problem in low- and middle-income countries [ 1 ]. Early childhood is a critical window for children’s physical and mental development and LBW contributes as a leading cause of illness and death among children during this period [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The birth weight of a newborn is a major public health problem, which affects an estimated 20 million babies born annually and is more common in low-middle-income countries (LMICs) [ 2 ]. Of these, 28% are born in South Africa, 13% in Sub-Saharan Africa, and 9% in Latin America [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The birth weight of a newborn is a major public health problem, which affects an estimated 20 million babies born annually and is more common in low-middle-income countries (LMICs) [ 2 ]. Of these, 28% are born in South Africa, 13% in Sub-Saharan Africa, and 9% in Latin America [ 2 ]. A recent study by Sathi et al showed that, in comparison to other LMICs in South Asia, the prevalence of LBW recorded in Afghanistan, Bangladesh, Nepal, and Pakistan was 15.13%, 14.93%, 11.73%, and 19.18%, respectively [ 3 ].…”
Section: Introductionmentioning
confidence: 99%